Balancing resources: Returns and the digital transformation of Vietnam’s banking sector - Anh, Nguyen Thi Lan; Nguyen, Duy Van (The Economics and Finance Letters, 2026)
Research on digital transformation plays a crucial role for enterprises, especially those in emerging economies such as Vietnam. This study aims to examine the impact of digital transformation, measured through the ICT index, on bank performance (ROE, ROA) during the period 2015–2022, involving 26 commercial banks listed on the Vietnam Stock Exchange. The results of the Feasible Generalized Least Squares (FGLS) regression analysis indicate that the ICT index of the previous year has a negative impact on bank performance. This finding suggests that the Resource-Based View (RBV) theory can provide a sound explanation for this relationship. Specifically, while banks make significant investments in digital transformation, the limited availability of resources may generate high costs, thereby negatively affecting bank performance in the short term. Based on these results, the authors also provide several theoretical and practical implications for enhancing bank performance through digital transformation. Establishing a clear roadmap that aligns with current capabilities can help banks avoid unnecessary costs during the digital transformation process. This study will make a significant theoretical contribution by explaining the impact of digital transformation on bank performance in Vietnam. Consequently, banks and relevant agencies can develop appropriate resource-balancing policies to promote the effectiveness of digital transformation.